Affective Control in New Collaborative Work: Communal Fantasies of Purpose, Growth and Belonging. Issue 5 (May 2021) - Resch, Bernhard; Hoyer, Patrizia; Steyaert, Chris
We examine the increasing popularity of collaborative work to understand the consequences of these practices for organizational control. Applying a Lacanian framework, we pay attention to how this (re-)emerging trend of collaborative work is underpinned by affect-laden fantasies of community-driven co-creation. Based on a multi-source study design to explore collaborative work, we identified three interrelated fantasies that arouse passionate attachments to collaborative community involvement: a spiritual fantasy of 'purpose', an entrepreneurial fantasy of 'growth' and a tribal fantasy of 'belonging'. To preserve the relevance of Lacan's thought for the inquiry of distributed, post-heroic and post-hierarchical work practice, we propose the notion of 'communal Other'. This notion provides insights into the unfolding of control through the fantasmatic desire for wholeness by working in collaborative communities. Conceptually, we theorize how tensions between the paradoxical enjoyment of pleasure and pain – what Lacan called 'jouissance' – highlight the central importance of affective control in collaborative work.